Laser Applications in Orthodontics - Heidari, Somayeh; Torkan, Sepideh (Journal of Lasers in Medical Sciences, 2013)
A laser is a collimated single wavelength of light which delivers a concentrated source of energy. Soon after different types of lasers were invented, investigators began to examine the effects of different wavelengths of laser energy on oral tissues, routine dental procedures and experimental applications. Orthodontists, along with other specialist in different fields of dentistry, can now benefit from several different advantages that lasers provide during the treatment process, from the beginning of the treatment, when separators are placed, to the time of resin residues removal from the tooth surface at the end of orthodontic treatment. This article outlines some of the most common usages of laser beam in orthodontics and also provides a comparison between laser and other conventional method that were the standard of care prior to the advent of laser in this field.